(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was conducted in two districts of Assam namely Lakhimpur and Sonitpur on the mode of selling of broiler birds at producer level. The study revealed that majority of the respondents in both districts (45.45 percent in Lakhimpur and 49.43 percent in Sonitpur) preferred marketing broiler birds through wholesaler by cash transaction. It was found that the price fixation of broiler depended upon the market demand and supply in both districts. Majority of the respondent in Lakhimpur district (62 percent) and in Sonitpur district used hired Vehicle for transportation of broiler birds.